COMPARISON OF SAGITTAL SPINAL CURVATURES AND PELVIC TILT IN HIGHLY TRAINED ATHLETES FROM DIFFERENT SPORT DISCIPLINES (Kinesiology, 2017)
The aim of this study was to compare the thoracic and lumbar curvatures and pelvic tilt in relaxed standing and maximal trunk flexion among highlytrained young athletes from three different sports disciplines. Thirty-two male canoeists, 30 male kayakers and 24 male tennis players were recruited for the study. The Spinal Mouse® system was used to measure the thoracic and lumbar sagittal spinal curvatures and pelvic tilt in relaxed standing and maximal trunk flexion in sitting with the flexed (McRae & Wright test) and extended knees (sit-and-reach test). Significant differences were found in maximal trunk flexion tests among athletes. Kayakers and canoeists showed increased anterior pelvic tilt compared to tennis players in the McRae & Wright (p